The Prospects for the Therapeutic Implications of Genetically Engineered Probiotics. (7th April 2020) - Mazhar, Sayyeda Farwa; Afzal, Muhammad; Almatroudi, Ahmad; Munir, Samman; Ashfaq, Usman Ali; Rasool, Maria; Raza, Hammad; Munir, Hafiz Muhammad Waqas; Rajoka, Muhammad Shahid Riaz; Khurshid, Mohsin
Abstract : The interest in the therapeutic use of probiotic microorganisms has been increased during the last decade although the doubts have ascended about the probiotics mainly because their beneficial effects are not fully understood, and, in many cases, their usefulness has not been validated in clinical trials. Consequently, the notion got a considerable interest in those strains having proven probiotic potential to be engineered for improvement in their beneficial features. The process of genetic engineering can also be used for probiotic strains for the reversion of antimicrobial resistance and other modifications for their safer and effective human applications. The lactic acid bacilli are predominantly opposite as they already have gained attention owing to their health-promoting benefits and their safety for human consumption; therefore, their use, especially as a delivery agent of vaccines and drugs, is gaining attention. The tailoring of probiotic strains will not only improve the data regarding the probiotic potential of these strains but also clinch the doubts concerning these probiotics. This article focuses on the approaches of bioengineered probiotics and discusses the potential prospects for their therapeutic applications including immunomodulation, cognitive health, and anticancer therapeutics.